70 years of Sergey V. Gonchenko - Kazakov, Aleksej Olegovich; Turaev, D. V. (Известия высших учебных заведений: Прикладная нелинейная динамика, 2023)
May 10, 2023 marks the 70th birthday of Professor Sergey Vladimirovich Gonchenko, a leading researcher of Lobachevsky State University of Nizhny Novgorod.